Analysis of Several Factors Affecting Labor Force Absorption in East Java Province for the Years 2017 - 2022 - Safitri, Fera Nurlaila; Suhartono, Edy (Gorontalo State University, 2024)
Evaluating the government's success in economic development is essential to assess how effectively the government can address unemployment and enhance job opportunities. To ensure that the workforce is optimally absorbed, it must be accompanied by the creation of new and abundant job opportunities. Labor issues are a common concern in developing countries like Indonesia, which has a large population. A significant population size leads to a substantial labor force, resulting in a high number of job seekers and unemployed individuals, which in turn leads to relatively low incomes. This research aims to analyze several factors influencing labor force absorption in East Java from 2017 to 2022. This research method utilizes secondary data, which consists of a 6-year panel data from 2017 to 2022. The analytical method employed in this research is multiple linear regression. The results of this research indicate that the minimum wage and economic growth do not have a significant impact on labor force absorption in East Java Province. On the other hand, the average years of schooling have a considerable influence on labor force absorption in East Java Province. This research serves as valuable input for determining the direction and future development strategies and can be used as a reference for predicting the labor force conditions in East Java. The imbalance between the large labor force and available job opportunities in East Java highlights the need for the government to focus more on labor force absorption in the province. These three factors can serve as a guide for the government in addressing labor force issues, aiming to optimize labor force absorption and consequently boost economic growth in East Java Province.